A Pulmonary Embolism Response Team: initial experiences and future directions. (3rd June 2017) - Zern, Emily K.; Young, Michael N.; Rosenfield, Kenneth; Kabrhel, Christopher
ABSTRACT: Introduction : Acute pulmonary embolism (PE) is a common cardiovascular condition resulting in significant morbidity and mortality. Consensus recommendations suggest risk stratification of patients into three main categories: high-risk or 'massive' PE, intermediate-risk or 'submassive' PE, and low-risk PE. Given the relative dearth of prospective, randomized clinical trials delineating optimal selection of the diverse medical, interventional, and surgical treatment approaches, clinical care requires a multidisciplinary expert approach to patients with PE. Areas covered : The Massachusetts General Hospital (MGH) Pulmonary Embolism Response Team (PERT) was the first of its kind to create a multidisciplinary, rapid response team for acute PE, integrated within a research and educational framework. The MGH PERT has treated more than 700 patients with PE, the majority of which are in the 'massive' or 'submassive' categories. The PERT Consortium™ was founded in 2015 as a collaborative network between the growing number of PERT programs internationally, with greater than 80 institutions participating within one year of establishment. Expert commentary : Since its advent, the PERT model has expanded throughout the United States and internationally through a collaborative institutional and research network. PERT may represent a new standard for the care of patients with acute PE.